The Influence of Free Shipping Tagline on Online Purchase Decision: A Case Study of Students in the Sharia Business Management Program at Muhammadiyah University of North Sumatra - Najih, Muhammad; Edi, Sarwo (SEAN Institute, 2024)
This study delves into the impact of the